Aufweichen, abbremsen, abschirmen - Wirtschaftsmetaphern zwischen politischer Abgrenzung und diskursiven Allgemeinplätzen [Forschungsdaten] - Barkhausen, David; Bloching, Sven; Engeler, Hannah (Universität, 2023)
Our study examines the use of metaphors in the German discourse regarding European monetary and fiscal policy. Though this policy area sparked cons...
Gesehen am 23.03.2023
Keywords: Forschungsdaten; Datenbank